2008
DOI: 10.1093/chemse/bjm084
|View full text |Cite
|
Sign up to set email alerts
|

Supertasting and PROP Bitterness Depends on More Than the TAS2R38 Gene

Abstract: Polymorphisms in the TAS2R38 gene provide insight to phenotypes long associated 6-n-propylthiouracil (PROP) and phenylthiocarbamide bitterness. We tested relationships between TAS2R38 genotype, taste phenotype, and fungiform papillae (FP) number in 139 females and 59 males (age range 21-60 years), primarily of European ancestry. DNA was analyzed for 3 polymorphic sites, identifying common (alanine-valine-isoleucine [AVI/AVI], heterozygotes, proline-alanine-valine [PAV/PAV]) and rare (proline-valine-isoleucine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
254
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(295 citation statements)
references
References 49 publications
39
254
2
Order By: Relevance
“…001). This is lower than previous reports (55-85%) (50,51) but may represent a truer estimation of the extent of the influence of this single gene on taste perception in a genetically diverse population, and is consistent with the recent finding that supertasting is dependent on more than simply the TAS2R38 gene (63) .…”
Section: Taste Perception and Food Choicesupporting
confidence: 87%
“…001). This is lower than previous reports (55-85%) (50,51) but may represent a truer estimation of the extent of the influence of this single gene on taste perception in a genetically diverse population, and is consistent with the recent finding that supertasting is dependent on more than simply the TAS2R38 gene (63) .…”
Section: Taste Perception and Food Choicesupporting
confidence: 87%
“…Anatomical studies reported that tasters actually have more taste buds than non tasters [24] and another study has showed positive relationship between the bitter perception to the number of fungiform papillae [25] present on the anterior surface of tongue.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previously reported phenotype-genotype relationships ranging from 55% to 85%. 13,38 Other factors including the number of fungiform papillae 14,39 and TAS2R38 receptor mRNA expression in taste cells 40 may play a role in defining PROP phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…8 Phenotypic variation in PROP/PTC taste sensitivity is controlled by sequence variation in the bitter receptor gene TAS2R38 that accounts for a major portion (55%-85%), but not all of the variance in sensitivity. 13,14 Polymorphisms in TAS2R38 code for two common haplotypes, PAV (the sensitive form) and AVI (the insensitive one). Several rare forms (e.g., AAI, AAV) also exist and are typically associated with intermediate sensitivities.…”
Section: Original Investigationmentioning
confidence: 99%